Overexpression of Raf-1 in basal-like carcinoma of the breast: correlation with clinicopathology and prognosis - Wu, Ping; Li, Xizhou; Wu, Yangmei; Hu, Wei; Wang, Yang; Gao, Li; Chen, Zhongzhong; Zheng, Weiqiang (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : Increased Raf-1 expression has been associated with an aggressive behaviour in some carcinomas such as pulmonary carcinoma and renal carcinoma. However, its role in breast cancer, especially in basal-like carcinoma of the breast (BLBC), has not been defined. Material and methods: The current study attempted to investigate the expression pattern of Raf-1 protein in BLBC, in relation to the biological behaviour and prognosis of the carcinoma. Expression of Raf-1 was detected by immunohistochemistry in carcinoma specimens from 74 cases of BLBC, and associations between their expression and the clinicopathological characteristics were statistically assessed. Results: The patients’ age, tumour size, BRCA1, and p53 protein expression was not significantly different between the Raf-1-positive and Raf-1-negative expression groups (p > 0.05). The proportion of histological grade 3 tumours was not significantly higher in the Raf-1 positive group than that of grade 2 tumours (p > 0.05). However, positive cytoplasmic Raf-1 expression was positively correlated to Ki-67 expression (p < 0.05). Also, increased Raf-1 protein was found to exert an unfavourable impact on patients’ axillary lymph node metastasis and overall survival (p < 0.05). Conclusions : The study implies that positive Raf-1 expression in BLBC is associated with a more aggressive phenotype and could be considered as a new prognostic biomarker for poor survival in BLBC patients.